Every student's guide to the world wide web - Pitter, Keiko (McGraw-Hill, 1997)
This brief, step-by-step guide to navigation on the World Wide Web uses Microsoft's Internet Explorer Web browser. Students are given the basic concepts behind the Web, shown how to get onto the Web, and pointed to some of the most dynamic and useful Web sites. Students will learn how to access information and strategies for locating additional resources.